Longer leukocyte telomere length in Costa Rica's Nicoya Peninsula: A population-based study - Rehkopf, David H. (2013)
Studies in humans suggest that leukocyte telomere length may act as a marker of biological aging. We investigated whether individuals in the Nicoya region of Costa Rica, known for exceptional longevity, had longer telomere length than those in other parts of the country. After controlling for age, age squared, rurality, rainy season and gender, mean leukocyte telomere length in Nicoya was substantially longer (81 base pairs, p<0.05) than in other areas of Costa Rica, providing evidence of a biological pathway to which this notable longevity may be related. This relationship remains unchanged (79 base pairs, p<0.05) after statistically controlling for nineteen potential biological, dietary and social and demographic mediators. Thus the difference in mean leukocyte telomere length that characterizes this unique region does not appear to be explainable by traditional behavioral and biological risk factors. More detailed examination of mean leukocyte telomere length by age shows that the regional telomere length difference declines at older ages.